Unusual polar ordering and room-temperature blue phase stabilization in tetrafluorinated bentshaped mesogens - Vij, Jagdish; Yadav, Neelam; Sahai, Mudit (Royal Society of Chemistry, 2025)
The growing demand for advanced photonic and electro-optical devices necessitates the rational design of novel functional materials. Liquid crystals (LCs) are particularly promising due to their highly tunable electro-optical properties. Building on this potential, we synthesized a series of polar bent-core LCs, F4-na (dipole moment ∼9.4 D), featuring a tetrafluorinated terminal motif and varying terminal chains. Distinct structure–property relationships are observed in this series of compounds, with the shorter chain homologues forming polar cybotactic clusters (Ncyb phase) alongside nematic and tilted smectic phases. Dielectric spectroscopy reveals non-trivial dipolar ordering, attributed to short-range polar order within cybotactic clusters, notably present without net macroscopic polarization. Under an AC field, the materials form electroconvection patterns, suggesting potential for optical modulation devices. Furthermore, the F4-na materials, particularly the lower homologues showing cybotactic clusters, stabilize the otherwise unstable blue phase (BP) at room temperature when doped with a chiral additive, achieving a maximum BP range of 22.9 °C. This overcomes the challenges in achieving room-temperature BP with our easily synthesizable materials, holding strong potential for 3D photonic applications. Overall, our findings offer promising opportunities for advancing room-temperature photonic and electro-optical devices while enhancing the understanding of self-assembly in soft functional materials.
PUBLISHED
10.1039/D5SC01530H
Keywords: Nanoscience & Materials; Electronic Materials